Proton pump inhibitor use: systematic review of global trends and practices - Shanika, Lelwala Guruge Thushani; Reynolds, Andrew; Pattison, Sharon; Braund, Rhiannon (European journal of clinical pharmacology, 2023)
Purpose Proton pump inhibitors (PPIs) reduce acid secretion in the stomach and rank as one of the most widely used acid-suppressing medicines globally. While PPIs are safe in the short-term, emerging evidence shows risks associated with long-term use. Current evidence on global PPI use is scarce. This systematic review aims to evaluate global PPI use in the general population. Methods Ovid MEDLINE, Embase, and International Pharmaceutical Abstracts were systematically searched from inception to 31 March 2023 to identify observational studies on oral PPI use among individuals aged ≥ 18 years. PPI use was classified by demographics and medication factors (dose, duration, and PPI types). The absolute numbers of PPI users for each subcategory were summed and expressed as a percentage. Results The search identified data from 28 million PPI users in 23 countries from 65 articles. This review indicated that nearly one-quarter of adults use a PPI. Of those using PPIs, 63% were less than 65 years. 56% of PPI users were female, and “White” ethnicities accounted for 75% of users. Nearly two-thirds of users were on high doses (≥ defined daily dose (DDD)), 25% of users continued PPIs for > 1 year, and 28% of these continued for > 3 years. Conclusion Given the widespread use PPIs and increasing concern regarding long-term use, this review provides a catalyst to support more rational use, particularly with unnecessary prolonged continuation. Clinicians should review PPI prescriptions regularly and deprescribe when there is no appropriate ongoing indication or evidence of benefit to reduce health harm and treatment cost.